Research data management and the evolutions of scholarship: Policy, infrastructure and data literacy at KU Leuven - Willaert, Tom; Cottyn, Jacob; Kenens, Ulrike; Vandendriessche, Thomas; Verbeke, Demmy; Wyns, Roxanne (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
This case study critically examines ongoing developments in contemporary scholarship through the lens of research data management support at KU Leuven, and KU Leuven Libraries in particular. By means of case-based examples, current initiatives for fostering sound scientific work and scholarship are considered in three associated domains: support for policy-making, the development of research infrastructures, and digital literacy training for students, scientists and scholars. It is outlined how KU Leuven Libraries collaborates with partner services in order to contribute to KU Leuven’s research data management support network. Particular attention is devoted to the innovations that facilitate such collaborations. These accounts of initial experiences form the basis for a reflection on best practices and pitfalls, and foreground a number of pertinent challenges facing the domain of research data management, including matters of scalability, technology acceptance and adoption, and methods for effectively gauging and communicating the manifold transformations of science and scholarship.